Sacralization Religion, Power Elite And Leadership: Female Regents In East Java - Nurul Azizah (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The involvement of the local Islamic boarding school (Pesantren) elite in a regional head election in East Java becomes the winning determiner. In a direct local election, elite religious roles significantly influence the constituent's vote. The elite utilizes religious hegemony in increasing society's political participation during an election. The era of new religious movement changes the tendencies of the thinking paradigm that, for the first time, women emerge as regional heads. This paper was aimed to analyze the hegemony of the religious elite based on Pesantren in the postmodernism era in regional head elections, especially in East Java. This research used qualitative research with a descriptive perspective and content analysis of qualitative data, which revealed that there is hegemony and patron-client movement of Islamic boarding school (Pesantren) among kyai, students, alumni, sympathizers, and Pesantren communities as a strategy to win regional head. The researcher used the elite theory approach and political participation theory—research data obtained from the library and document analysis from the affiliated institution. The formulation of this problem is how the religious elite hegemony the societies by increasing public participation and convincing voters to vote for women's candidates as governor. The analysis result remarks the hegemony of the religious elite becomes a tool to obtain power in a regional head election because there are significant influences of religious elite functioning giving dogmatize to society through religious routines ritual such as religion speech